Surgical management of inverted papilloma; a single-center analysis of 247 patients with long follow-up - Oisín Bugter; Dominiek André Monserez; Floris Vincent Willem Joseph van Zijl; Robert Jan Baatenburg de Jong; Jose Angelito Hardillo (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Our aim was to review our management of inverted papilloma (IP), perform a recurrence analysis, and review the literature. Methods A retrospective analysis of 247 patients treated for an IP. Patients were grouped according to surgical approach, tumor presentation (primary, residual and recurrence) and Krouse-stage. Results Recurrence was observed in 20.3%, 28.6% and 35.1% (p = 0.017) of the patients who underwent endoscopic, external and combined surgery, respectively. Recurrences occurred more often in residual than primary IP (36.9% vs. 22.3%, p = 0.021). Primary endoscopic surgery had a recurrence rate of 12.5%, which was comparable to the recent literature (11.2%, 161/1433). Conclusions The relatively high number of recurrences in this cohort is explained by the long follow-up and previous (incomplete) surgery in 61.5% of the cases. The inferior outcome of residual IP underscores the importance of having a low threshold for preoperative biopsy in unilateral and atypical sinonasal disease.